Association study between GAS6 gene polymorphisms and risk of preeclampsia in Chinese population. (April 2017) - Ye, Liyan; Guan, Linbo; Fan, Ping; Liu, Xinghui; Liu, Rui; Chen, Jinxin; Zhu, Yue; Wei, Xing; Liu, Yu; Bai, Huai
Abstract: Context and objective: Preeclampsia is a pregnancy-specific disorder associated with pro-inflammatory and pro-thrombotic events. The growth arrest-specific 6 (GAS6) has been implicated in systemic inflammation and coagulation. Common genetic polymorphisms of GAS6 gene have previously been reported. The aim of this study was to investigate the association of GAS6 gene polymorphisms with the risk of preeclampsia in Chinese subjects. Study design: The case–control population consists of 551 subjects. The genotyping of the single-nucleotide polymorphisms of GAS6 gene, GAS6 834 +7G/A(rs8191974) and +1332C/T (rs1803628), was carried out on genomic DNA using polymerase chain reaction-restriction fragment length polymorphisms (PCR-RFLP) analysis. Results: There were significant differences in the +1332C/T genotype and allele frequencies between the patients with preeclampsia and the controls (P = 0.03 and 0.02, respectively). The +1332 TT genotype was found to be protective from the development of preeclampsia (odds ratios 0.271, 95% confidence interval 0.077–0.953; P = 0.03). Further analysis showed that the TT genotype of the GAS6 +1332C/T conferred a risk of severe preeclampsia (OR = 0.597, 95% confidence interval 0.416–0.855; P = 0.01). However, there were no differences in the 834 + 7G/A genotype and allele frequencies between the patients with preeclampsia and the controls. Conclusion: Our data suggest that a TT genotype at +1332C/T polymorphism might be associated with decreased risk for preeclampsia, but the 834 + 7G/A polymorphism is not associated with the disorder, in the Chinese population.